A single cell atlas of the human liver tumor microenvironment - Hassan Massalha; Keren Bahar Halpern; Samir Abu‐Gazala; Tamar Jana; Efi E Massasa; Andreas E Moor; Lisa Buchauer; Milena Rozenberg; Eli Pikarsky; Ido Amit; Gideon Zamir; Shalev Itzkovitz (Molecular Systems Biology)
Abstract Malignant cell growth is fueled by interactions between tumor cells and the stromal cells composing the tumor microenvironment. The human liver is a major site of tumors and metastases, but molecular identities and intercellular interactions of different cell types have not been resolved in these pathologies. Here, we apply single cell RNA‐sequencing and spatial analysis of malignant and adjacent non‐malignant liver tissues from five patients with cholangiocarcinoma or liver metastases. We find that stromal cells exhibit recurring, patient‐independent expression programs, and reconstruct a ligand–receptor map that highlights recurring tumor–stroma interactions. By combining transcriptomics of laser‐capture microdissected regions, we reconstruct a zonation atlas of hepatocytes in the non‐malignant sites and characterize the spatial distribution of each cell type across the tumor microenvironment. Our analysis provides a resource for understanding human liver malignancies and may expose potential points of interventions.